(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
According to Husserl there is not only a negative meaning of scepticism, in which reason dissolves itself in an exasperated relativism, but also a completely opposite one, in which the idea of scepticism is a necessary transition for rational argumentation that reflects the actual ability of radically questioning those certainties that are fideistically interwoven in the relationship between life and scientific knowledge. It is therefore equally unquestionable that the objective of such scepticism is to seek, with untiring fatigue, solid, persuasive terrain for one’s own argumentation that has the constant backdrop of revealing a new idea of subjectivity in its intrinsic tie with science and the common world of practical life. These two forms of scepticism, the anti-philosophical and the critical-rational therefore share an important trait: their unavoidable reference to subjectivity. However, whilst the discovery of the absolute intimacy of subjectivity with the world as a theatre of cognitive operations and of the creation of meaning fills the alleged fracture of a reality in itself that transcends the subject, it does not however eliminate the actual reasons of the concrete existence of the world and of the actual influence of such a reality on operations in the process of their creation. It is this that is the crucial question, the essential correlation between self and world, which progressively gains more and more importance in the evolution of Husserl’s notion of epoché and phenomenological reduction. A notion that corresponds to the critical exercise of reason, the necessary exercise of a scepticism that is never exhausted in itself as it never exhausts the view of the constantly changing meaning of the world in the wealth of its infinite essential traits.